High-throughput screening of natural compounds for prophage induction in controlling pathogenic bacteria in food - Tompkins, Elizabeth; Cadieux, Brigitte; Amitrano, Margot; Goodridge, Lawrence (Frontiers in Food Science and Technology, 2023)
Introduction: The clean label trend emphasizes the need for natural approaches to combat pathogenic bacteria in food. This study explores the potential of inducing prophages within bacterial genomes as a novel strategy to control pathogenic and spoilage bacterial growth. Methods: A luminescence-based high-throughput assay was developed to identify natural compounds capable of inducing prophages. Bioactive compounds from four chemical libraries were screened at a final concentration of 10 µM. The assay measured luminescence production in Escherichia coli BR513, a genetically modified strain producing β-galactosidase upon prophage λ induction. Luminescence values were normalized to cell concentration (OD600) and the interquartile mean of each 384-well plate. A cut-off for normalized luminescence values, set at 2.25 standard deviations above the mean, defined positive prophage induction. Results: Four naturally-derived compounds (osthol, roccellic acid, galanginee, and sclareol) exhibited positive prophage induction, along with previously identified inducers, rosemary, and gallic acid. Dose-response experiments were conducted to determine optimal concentrations for prophage induction. However, the results could not distinguish between prophage-induced cell death and other mechanisms, making it challenging to identify ideal concentrations. Discussion: The high-throughput luminescent prophage induction assay serves as a valuable tool for the initial screening of natural bioactive compounds that have the potential to enhance food safety and quality by inducing prophages. Further research is required to understand the mechanism of bacterial cell death and to establish optimal concentrations for prophage induction in a food preservation context.